The orthography from grandfather anecdotal stories - Becerra Peña, Samuel; Martínez Quiroga, Luis Orlando; Bolívar Suárez, Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Through the experience of the authors, it is possible to infer that the anecdotes of the grandfather, specifically the one titled: “Diánchiro de Carboneras”, provides some strategies in the orthographic teaching of the oxytone words finished in a vowel, and gives rise to writing of the present reflexive article, which aims to show the incidence of the story mentioned in the learning of the ticked in a fifth grade student in Carboneras rural branch, of the educational institution Juana Caporal in Coper (Boyacá, Colombia). Through the support of theoretical referents and the application of activities from the anecdote, which was contributed by the aforementioned student, the relationship of the anecdote with the teaching of the orthography of oxytone words is shown, implementing activities that can be appreciated with precision in the methodological handle of the present article. The anecdote is told in a verb tense (simple past tense), which allows a practical understanding of the subject matter addressed here. As a result of learning to use the accentuation of these words, text writing with greater sense and coherence has been evidenced.